Evaluation of the Cakap Baca Program Using the Kirkpatrick Model at SMP Negeri 1 Banjarmasin - Azmy, M. Noor; Utama, Agus Hadi; Mastur, Mastur; Nurdin, Encep Syarief; Maftuh, Bunyamin (Jurnal Evaluasi dan Pembelajaran, 2025)
The Cakap Baca literacy program is a program that has been implemented at SMP Negeri 1 Banjarmasin as part of the Teaching Assistance activities. This literacy program falls under the category of basic literacy, specifically reading literacy. This study aims to evaluate the effectiveness of the Cakap Baca program at SMP Negeri 1 Banjarmasin, which is designed to improve participants’ abilities to understand, analyze, and evaluate reading texts, using the Kirkpatrick evaluation model. The method used is qualitative, employing the model developed by Donald Kirkpatrick, which consists of four levels: reaction, learning, behavior, and results. Data were collected through observation, interviews, and document studies. Observations were conducted in stages: during the preparation of the teaching assistance work program, during the implementation of the Cakap Baca program, and after the program was completed. Interviews were conducted throughout the research process, involving 27 students and 2 educators as respondents to obtain in-depth data about their experiences and perceptions of the program. Document studies focused on analyzing students’ work as material for evaluating the program’s success. The study showed positive results across all four levels of the Kirkpatrick evaluation. At the reaction level, students responded enthusiastically and enjoyed the fun and interactive methods. At the learning level, there was an improvement in reading ability and communication skills, although challenges remained in summarizing and critical thinking. At the behavior level, positive changes were observed in reading habits and increased visits to the school’s literacy facilities, although ongoing support is still needed. At the results level, the program impacted the improvement of subject comprehension, especially in Indonesian language, and encouraged the growth of a literacy culture. The positive outcomes of the Cakap Baca program demonstrate its potential as a sustainable literacy initiative that effectively enhances reading skills and fosters a culture of literacy among students. Further support and development are necessary to address challenges in critical thinking and summarizing skills.